Śākaạ̄yana-vyākaraṇam : svopajña-amoghavt̥tisamalaṅkr̥tam - Śākaṭāyana, 9th cent (Jñānapīṭha Mūrtidevī Jaina granthamālā. Samskr̥ta granthāṅka ;, 1971)
Treatise on Sanskrit grammar in aphorisms with autocommentary; critical edition.